Effect of yoga asanas on flexibility among taekwondo players in India - Marina Rai; P Yoga; K Alaguraja (Davao Research Journal)
The purpose of the present study was to investigate the effect of yoga asanas on flexibility among taekwondo players. Thirty (30) male taekwondo players who participated in the state-level competition were selected randomly from Tamil Nadu, India. The subject’s age ranges from 18 to 25 years. The selected subjects were divided into two equal groups consisting of 15 subjects-the experimental and control groups. The experimental group underwent yoga asanas for ten weeks. The control group did not take part in any training during the course of the study. Flexibility was taken as a criterion variable in this study. The selected subjects were tested on flexibility and were measured through sit and reach tests. A pre-test was taken before the training period, and a post-test was measured immediately after the ten-week training period. Statistical technique t-ratio was used to analyze the means of the pre-test and post-test data of the experimental and control groups. The results revealed a significant difference found in the criterion variable. The difference is found due to combined yoga asanas given to the experimental group on flexibility when compared to the control group.